2007
DOI: 10.1093/jn/137.5.1161
|View full text |Cite
|
Sign up to set email alerts
|

Nonheme Iron Absorption in Young Women Is Not Influenced by Purified Sulfated and Unsulfated Glycosaminoglycans

Abstract: Meat is a well-known enhancer of iron absorption, yet the molecular entity mediating the effect remains obscure. Recently published data indicate that highly acidic sulfated glycosaminoglycans (GAG) from fish and chicken muscle are effective stimulants of iron uptake in Caco-2 cells. Two fully randomized stable isotope studies with crossover design were performed in a group of 16 apparently healthy young women to assess the effect of purified sulfated and unsulfated GAG on human iron absorption. Iron absorptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Different types of glycosaminoglycans (GAG), which are part of the connective tissue between muscle fibers, have also been the subject of investigations. However, although GAGs promoted iron uptake in Caco-2 cells [ 185 , 186 ], a human study failed to show an effect on iron absorption [ 187 ]. Armah and colleagues [ 188 ] have also suggested that phosphatidyl choline contributes to the enhancing effect of meat.…”
Section: Resultsmentioning
confidence: 99%
“…Different types of glycosaminoglycans (GAG), which are part of the connective tissue between muscle fibers, have also been the subject of investigations. However, although GAGs promoted iron uptake in Caco-2 cells [ 185 , 186 ], a human study failed to show an effect on iron absorption [ 187 ]. Armah and colleagues [ 188 ] have also suggested that phosphatidyl choline contributes to the enhancing effect of meat.…”
Section: Resultsmentioning
confidence: 99%
“…With respect to the meat factor that enhances non-haem iron absorption, many constituents have been studied: amino acids ( 35 , 36 ) , animal protein ( 37 40 ) and carbohydrate fractions ( 17 , 41 ) . From acid extracts of fish, heparin-like glycosaminoglycans increased iron uptake in an in vitro digestion/Caco-2 cell model ( 17 ) ; the active fractions were identified as the low-molecular-weight carbohydrate degradation products of the glycosaminoglycans.…”
Section: Discussionmentioning
confidence: 99%
“…From acid extracts of fish, heparin-like glycosaminoglycans increased iron uptake in an in vitro digestion/Caco-2 cell model ( 17 ) ; the active fractions were identified as the low-molecular-weight carbohydrate degradation products of the glycosaminoglycans. A human bioavailability study with purified glycosaminoglycans that were not acid-extracted found no improvements in iron bioavailability compared to a semi-synthetic meal with no glycosaminoglycans ( 41 ) . The key to glycosaminoglycans improving iron bioavailability may lie with their acid extraction from a food source ( 42 ) .…”
Section: Discussionmentioning
confidence: 99%